A REVIEW ON THE COMPARATIVE STUDY BETWEEN THE PRECAST AND CONVENTIONAL BUILDING CONSTRUCTION - Tan, Let Hui; Ng, Chee Khoon; Ting, Sim Nee (Construction Research Institute of Malaysia (CREAM), 2021)
The precast building construction method emerged in Malaysia construction industry as an approach to accelerate the productivity. This paper aims to provide an overview on the critical elements used for the comparative studies in precast and conventional building construction methods. Previous research works are reviewed to identify the standardization in comparison between the chosen building systems and the critical elements contributing to the economic benefits. It is important to evaluate for the standard comparison between both construction methods in the assessment for better choice among the two-construction methods.